A Job, Indeed! Accessibility Equity to Advertised Employment in Cascadia - Jerome R Mayaud; Rohan Nuttall (Findings)
We build on established inequality evaluation methods to assess (in)equities in accessibility to advertised jobs in Portland, Seattle, and Vancouver. We demonstrate the value of using postings from the world’s largest classifieds platform, Indeed.com, to complement existing employment datasets in accessibility studies.